Factors associated with thrombosis among solid organ cancer patients in Kuala Lumpur, Malaysia - Lailatulema Abbas; Ibtisam Muhamad Nor; Fuad Ismail; Sivakumar Palaniappan; Guang Yong Chong; Sharifa Ezat Wan Puteh; Siti Afiqah Muhamad Jamil; Nor Rafeah Tumian (Thrombosis Journal)
Abstract Background Patients with solid organ cancers are at increased risk of developing cancer-associated thrombosis (CAT), a complication driven by a complex interplay of patient-specific factors, cancer characteristics, and treatment modalities. Data on CAT and its associated risk factors within diverse ethnic groups, such as the Malaysian population, remains limited. This observational, cohort study aimed to address this gap by determining the incidence of CAT and identifying associated risk factors among multi-ethnic Malaysian patients with solid organ cancers. Methods This study included solid organ cancer patients aged ≥ 18 who attended HCTM and HKL from May 2022 to August 2023. The baseline demographics, and clinical characteristics, were acquired at the cancer diagnosis. Data on cancer treatment, thrombotic events and anticoagulation therapy during the study and its treatment were documented. Multivariable logistic regression analysis was performed to determine the independent factors associated with CAT in solid organ cancer. Results A total of 250 solid organ cancer patients were included, with a mean age of 57.7 (13.7) years. This multi-ethnic cohort consisted of mostly Malay patients (55.2%), followed by Chinese (33.2%) and Indian & others (11.6%). The prevalence of CAT at baseline was 4.8%, while the incidence of CAT during follow-up was 12%. Poor performance status and obesity were associated with CAT at baseline. Univariable logistic regression showed platelets ≥ 450 × 109/L and Khorana score ≥ 3 had significantly higher risks of CAT at baseline. Stage IV disease, radiotherapy and chemotherapy, namely platinum-based chemotherapy and antimetabolites were associated with CAT during follow-up. The ROC analysis showed that the KRS significantly predicted CAT (area under the curve, 0.701 (95%CI: 0.594–0.808, p = 0.001). Conclusions This study highlights the prevalence of CAT at baseline and the incidence of CAT during follow-up, similar to other studies. Patients’ clinical characteristics were associated with CAT at baseline while disease and treatment factors were associated with CAT at follow-up. These findings emphasise the need for targeted thromboprophylaxis in high-risk populations and highlight the importance of risk stratification tools such as the Khorana score for optimal patient management. Future studies involving larger patient cohorts and longer study duration would be beneficial. These findings provide valuable insights to inform clinical decision-making, optimise patient outcomes, and minimise potential risks.